(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Non-profit organisations offer programmes that are not offered by the private or government sectors, such as capacity acquisition, job formation, and the creation of social integration pathways. Despite their widely recognised important contribution to society, there are few studies about how they handle their finances. Through comparing the financial accounting activities two non-profit organisations, one faith-based and the other community-based, this study expands the frontiers of awareness. The thesis took a field-based methodology, analysing the financial reporting activities of the study organisations by interviews, paper analysis, artefact analysis, and analysis of existing annual reports. The study discovered that, although both organisations are well conscious of the threats associated with financial reporting, they use various methods to minimise such risks. Despite the fact that they are not for profit, organisations that are not for benefit are encouraged to implement cost-cutting measures in order to justify their sponsorship from investors. Financial management goals are incorporated into the organization’s approach by strategic financial management.